ON THE DISTRIBUTION OF THE LATTICE BROWN, KIRINIA ROXELANA (CRAMER, 1777) IN SOUTHERN CROATIA (LEPIDOPTERA: NYMPHALIDAE) (Acta Entomologica Serbica, 2019)
New observations of lattice brown, Kirinia roxelana (Cramer, 1777) in southern Croatia are presented. The species has been recorded at 11 new localities across the mainland part of Dubrovnik-Neretva County. As the species inhabits mostly rural areas, more targeted surveys in such habitats are needed to provide additional records. The specificity of this habitat is also the main reason why the species has so rarely been observed in Croatia. New records represent an important addition to the knowledge of the distribution of this species and illustrate the lack of faunistic research in the region.